1973
DOI: 10.1104/pp.52.6.633
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Uptake by Pea Leaf Fragments

Abstract: Amino acid uptake into leaf fragments of Pisum sativum depended on metabolism. Glycine uptake was optimal at 30 C and could be supported by respiration and by photosynthesis. Based on studies with an electron flow cofactor, inhibitors, and uncouplers, the energy source for glycine uptake was apparently ATP.The energy-dependent transport of glycine was mediated by a carrier that had a broad specificity for neutral and positively charged L-amino acids. It readily translocated 15 such L-amino acids into the cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…The rates of transport over a wide concentration range do not conform to simple MichaelisMenten kinetics, resulting in various mechanistic interpretations (9,14,22). The energy dependence of transport is supported by the effects of metabolic inhibitors (4,9,14). The transport of small neutral amino acids is apparently mediated by a carrier with broad specificity (4, 9, 15); a number of other systems for basic, acidic, and neutral amino acids have been proposed (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of transport over a wide concentration range do not conform to simple MichaelisMenten kinetics, resulting in various mechanistic interpretations (9,14,22). The energy dependence of transport is supported by the effects of metabolic inhibitors (4,9,14). The transport of small neutral amino acids is apparently mediated by a carrier with broad specificity (4, 9, 15); a number of other systems for basic, acidic, and neutral amino acids have been proposed (15).…”
mentioning
confidence: 99%
“…The transport of amino acids into plant cells has been investigated using either sections of plant drgans (4,22,25) or isolated cells cultured in liquid medium (9,10,14,15). Some generalizations can be drawn from the limited literature.…”
mentioning
confidence: 99%
“…DISCUSSION The general characteristics of L-Arg, L-Asp, L-His, and L-Phe transport have been determined. In most respects, the transport of these amino acids is identical to that of L-Leu (4) and of other amino acids (7,8,10,15). That is, uptake is pH-dependent, energydependent, stereospecific, dependent upon culture growth phase, concentrative, and carrier-mediated, the exception being that LAsp is not concentrated.…”
Section: Resultsmentioning
confidence: 88%
“…Some researchers suggest a single system for all amino acids (6,7,10), while others suggest multiple systems (1,9,12). Cheung and Nobel (7) reported that L-Ala, L-Ser, L-Thr, L-Asp, and L-Glu competitively inhibited glycine uptake in pea leaf fragments and that Ki values were similar to Km values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation